Impact of COVID‐19 social restrictions on trauma presentations in South Australia. (8th November 2020) - Harris, Daniel; Ellis, Daniel Y; Gorman, David; Foo, Ngee; Haustead, Daniel
Abstract: Objective: To review the impact of COVID‐19 social restrictions on trauma presentations in South Australia. Methods: Retrospective database review. Results: During the period of social restrictions, there was a reduction in presentations of trauma and major trauma by 17% and 33%, respectively. The reduction in presentation rates was due to a large decrease in those aged over 40, with an increase in presentations in those younger than 40. Review by mechanism and location of injury revealed a reduction in road trauma, yet an increase in pedestrian trauma and trauma at home. Conclusion: Social restrictions alter the characteristics of trauma presentations.